Complement Activation in Inflammatory Skin Diseases - Giang, Jenny; Seelen, Marc A. J.; van Doorn, Martijn B. A.; Rissmann, Robert; Prens, Errol P.; Damman, Jeffrey (Frontiers in Immunology, 2018)
The complement system is a fundamental part of the innate immune system, playing a crucial role in host defense against various pathogens, such as bacteria, viruses and fungi. Activation of complement results in production of several molecules mediating chemotaxis, opsonization and mast cell degranulation, which can contribute to the elimination of pathogenic organisms and inflammation. Furthermore, the complement system also has regulating properties in inflammatory and immune responses. Complement activity in diseases is rather complex and may involve both aberrant expression of complement and genetic deficiencies of complement components or regulators. The skin represents an active immune organ with complex interactions between cellular components and various mediators. Complement involvement has been associated with several skin diseases, such as psoriasis, lupus erythematosus, cutaneous vasculitis, urticaria and bullous dermatoses. Several triggers including autoantibodies and micro-organisms can activate complement, while on the other hand complement deficiencies can contribute to impaired immune complex clearance, leading to disease. This review provides an overview of the role of complement in inflammatory skin diseases and discusses complement factors as potential new targets for therapeutic intervention.